Minat Nasabah Terhadap Tabungan Easy Wadiah Pada Bank Syariah Indonesia (BSI) KCP Medan Marelan - Suhailatun Nafisah; Ahmad Perdana Indra (LPPM Universitas Labuhanbatu, 2021)
This study aims to determine customer interest in easy wadiah savings and what factors influence customer interest in easy wadiah savings product at the Indonesia Islamic Bank (BSI) KCP Medan Marelan Raya. Wadiah savings are types of deposits from customers who require fund deposit services with a level of flexibility in withdrawing these funds. The data obtained in this study is the number of customers who are interested in opening wadiah savings at BSI in 2021 to 2022. Data analysis and discussion is by using descriptive methods by sistematically describing certain facts or characteristics carefully and thoroughly. While data collection using two days, namely interviewers and observations.